Promoting Vocational Training by Integrating Buddhist Principles for Prisoners of Thonburi Remand Prison Bangkok - Wongthep, Swat; (Plongkhun), PhrakruSutananthapandit Watcharapong; Khumpong, Worapat (Journal of Thammawat, 2025)
The purpose of this article was: 1) to study the level of promotion of vocational training for inmates at Thonburi Remand Prison; 2) to study the relationship between Buddhist principles and the promotion of vocational training for inmates at Thonburi Remand Prison; and 3) to study the problems, obstacles, and suggestions for promoting vocational training for inmates at Thonburi Remand Prison by integrating with Buddhist principles. Mixed-method research was used between quantitative research using survey research methods by collecting data from research questionnaires from 700 inmates of Thonburi Remand Prison, Zone 4 and Zone 5, aged 18 years and over, and qualitative research using in-depth interviews with key informants using specific random sampling, divided into 6 groups, 9 figures/person. The research revealed that: This study utilized a mixed-method approach to examine the promotion of vocational training for inmates at Thonburi Remand Prison, integrating Buddhist principles. The findings indicated a high overall level of vocational training promotion (= 4.63, S.D. = 0.66) and a strong positive relationship with Buddhist principles (r = .730, p < .01).